Numerical modelling of the influence of viscous fingering on the mechanical properties of structural adhesive joints - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson (The 16th International Conference on the Science and Technology of Adhesion and Adhesives)

Influence of the process time on a self-piercing riveting process with tumbling kinematic - Wituschek, Simon; Elbel, Leonie; Lechner, Michael (Proceedings of the Institution of Mechanical Engineers, Part E: Journal of Process Mechanical Engineering)

Lebendiges Silberschmiedehandwerk in Westfalen am Beispiel der 1892 gegründeten Werkstatt Cassau in Paderborn - Harnack, Maria (Graugold. Magazin für Alltagskultur)

Dialectical Jesus - Ficara, Elena (Paradox and Contradiction in Theology)

Hegelian Aristotelianism and the Philosophical Roots of Non-Classical Logics - Ficara, Elena (Aristotle's Organon in Old and New Logic)

Adopting Generative AI for Literature Reviews: An Epistemological Perspective - Schryen, Guido; Marrone, Mauricio; Yang, Jiaqi (Proceedings of the 57th Hawaii International Conference on System Science (HICSS 2024))

A Design Theory for Spontaneous Volunteer Coordination Systems in Disaster Response - Betke, Hans; Sperling, Martina; Schryen, Guido; Sackmann, Stefan (Proceedings of the 57th Hawaii International Conference on System Science (HICSS 2024))

Optical bias and cryogenic laser readout of a multipixel superconducting nanowire single photon detector - Thiele, Frederik; Lamberty, Niklas; Hummel, Thomas; Bartley, Tim (APL Photonics)
Cryogenic opto-electronic interconnects are gaining increasing interest as a means to control and readout cryogenic electronic components. The challenge is to achieve sufficient signal integrity with low heat load processing. In this context, we demonstrate the opto-electronic bias and readout of a commercial four-pixel superconducting nanowire single-photon detector array using a cryogenic photodiode and laser. We show that this approach has a similar system detection efficiency to a conventional bias. Furthermore, multi-pixel detection events are faithfully converted between the optical and electrical domains, which allows reliable extraction of amplitude multiplexed photon statistics. Our device has a latent heat load of 2.6 mW, maintains a signal rise time of 3 ns, and operates in free-running (self-resetting) mode at a repetition rate of 600 kHz. This demonstrates the potential of high-bandwidth, low noise, and low heat load opto-electronic interconnects for scalable cryogenic signal processing and transmission.

Towards Automated Design: Automatically Generating Modeling Elements with Prompt Engineering and Generative Artificial Intelligence - Kulkarni, Pranav Jayant; Tissen, Denis; Bernijazov, Ruslan; Dumitrescu, Roman (DS 130: Proceedings of NordDesign 2024)
Developing Intelligent Technical Systems (ITS) involves a complex process encompassing planning, analysis, design, production, and maintenance. Model-Based Systems Engineering (MBSE) is a key methodology for systematic systems engineering. Designing models for ITS requires harmonious interaction of various elements, posing a challenge in MBSE. Leveraging Generative Artificial Intelligence, we generated a dataset for modeling, using prompt engineering on large language models. The generated artifacts can aid engineers in MBSE design or serve as synthetic training data for AI assistants.
Keywords: Data Driven Design; Design Automation; Systems Engineering (SE); Artificial Intelligence (AI)

Spearhead Data-Driven Model-Based Systems Engineering: Interview Study on Definition, Preconditions, Challenges, Potentials, and Use Cases - Tissen, Denis; Wiederkehr, Ingrid; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (DS 130: Proceedings of NordDesign 2024, Reykjavik, Iceland, 12th - 14th August 2024)

A Maturity Model for Data-Driven Model-Based Systems Engineering for Producing Companies - Tissen, Denis; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (DS 134: Proceedings of the 26th International DSM Conference (DSM 2024), Stuttgart, Germany)

Democracy, the Internet, and Capitalism: A Reply to Elisabeth Korn and Jens Schröter. - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

PV Microinverters: Balcony Power Plants, Latest Efficiency Rankings, Yield Calculation for Overpowered Mini PV Systems - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 41st European Photovoltaic Solar Energy Conference)

Parameterized Complexity of Weighted Team Definability - Kontinen, Juha; Mahmood, Yasir; Meier, Arne; Vollmer, Heribert (Mathematical Structures in Computer Science)
Keywords: dice mahmood

Analyse von Kompetenzprofilen - Sandfort, Luc (Intelligente Technische Systeme – Lösungen aus dem Spitzencluster it’s OWL)

63 Use Cases for Analyzing Data in Product Management of Manufacturing Companies - Grigoryan, Khoren; Fichtler, Timm; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (AMCIS 2024 Proceedings)

Mesh‐ and model adaptivity for NTFA and full‐field elasto‐plastic homogenization based on downwind and upwind approximations - Tchomgue Simeu, Arnold; Mahnken, Rolf (PAMM)
Abstract To increase the quality of computational results for heterogeneous materials like fiber‐reinforced composites with Prandtl–Reuss‐type material laws, goal‐oriented measures of the adaptive finite element method coupled to model adaptivity is established. The former is an adaptive mesh refinement on the macroscale, which allows to control the spatial discretization errors. The latter is an efficient combination of a numerically low cost nonuniform transformation field analysis (NTFA) and numerically high cost full‐field elasto‐plastic homogenization methods on the microscale. The present contribution deals with the application of the concept of downwind and upwind approximations to a goal‐oriented a posteriori error estimator based on duality techniques by means of reduced order homogenization schemes like NTFA, and with accuracy and numerical efficiency of the proposed goal‐oriented adaptive framework. NTFA consists of an offline phase and an online phase. During the offline phase, some relevant information of the micro system under consideration is precomputed allowing a reduced set of equations to be solved in the online phase. Thus, NTFA leads to a quite efficient homogenization method but less accurate compared to the full‐field homogenization method which is characterized with a high computational demand for accounting nonlinear microstructural mechanisms. Due to nonlinearities and time‐dependency of plasticity, the estimation of error transport and error generation are obtained with a backward‐in‐time dual method despite a high demand on memory capacity. In this contribution, the dual problem is solved with a forward‐in‐time dual method that allows estimating the full error during the resolution of the primal problem without the need for extra memory capacity. Several numerical examples illustrate the effectiveness of the proposed adaptive approach based on downwind and upwind approximations.

EDGE: Evaluation Framework for Logical vs. Subgraph Explanations for Node Classifiers on Knowledge Graphs - Sapkota, Rupesh; Köhler, Dominik; Heindorf, Stefan (Proceedings of the 33rd ACM International Conference on Information and Knowledge Management (CIKM ’24),)

AutoCL: AutoML for Concept Learning - Li, Jiayi; Satheesh, Sheetal; Heindorf, Stefan; Moussallem, Diego; Speck, René; Ngonga Ngomo, Axel-Cyrille (Communications in Computer and Information Science)

„Es kann das Ganze nicht gelingen, wenn man nicht zusammenwirkt" - Die SoTL-Rundreise als communitybasiertes Interaktionsformat - Vöing, Nerea; Arnold, Maik; Weber, Stefka; Reisas, Sabine; Timmann, Anke (Co-kreatives Lernen und Lehren. Hochschulbildung im Zeitalter der Disruption)